In Vitro Antioxidant, Anti-Biofilm, and Solar Protection Activities of Melocactus zehntneri (Britton & Rose) Pulp Extract - Verônica Giuliani de Queiroz Aquino-Martins; Luciana Fentanes Moura de Melo; Larissa Marina Pereira Silva; Thales Rodrigo Targino de Lima; Moacir Fernandes Queiroz; Rony Lucas Silva Viana; Silvana Maria Zucolotto; Vania Sousa Andrade; Hugo Alexandre Oliveira Rocha; Katia Castanho Scortecci (MDPI AG, 2019)
Cactaceae plants are important due to their nutritional and therapeutic values. This study aimed to identify the phytochemical profile and biological activities of six Melocactus zehntneri pulp extracts: hexane extract (HE), chloroform extract (CE), ethanol extract (EE), methanol extract (ME), final water extract (FWE), and water extract (WE). Sugar, phenolic compounds, and protein content of the extracts were determined. Then thin layer chromatography (TLC) was performed to detect the presence of terpenes (ursolic and oleanolic acids), saponins, sugars, and glycoproteins. These extracts were analyzed for antioxidant activity via in vitro assay. HE showed 75% ferric chelating activity. All extracts showed 80−100% superoxide and hydroxyl radical-scavenging activities, respectively. Further, all extracts at 25 µg/mL showed 60% activity against DPPH. Moreover, in the 3T3 cells lines, no cytotoxicity was observed; however, therapeutic activity against the effects of the H2O2 treatment was exhibited. Finally, the polar extracts (EE, ME, FWE, and WE), particularly WE, elicited activity against the biofilms of Staphylococcus epidermidis, and HE and CE expressed a capacity for solar protection.